Kepemimpinan Transformasional Kepala Madrasah Dalam Implementasi Kurikulum Merdeka - VikaSari, Asri Yuni; Fauzi, Anis; Bahaf, Abdul Muin; Gunawan, Agus; Priatna, Suherman (El-Idare, 2023)
Leaders have a key role in dealing with curriculum changes. They are responsible for identifying new needs and motivating team members through transformational leadership. This research uses qualitative methods with library research, using primary data from documents and secondary data from national/international journals with the keywords "leadership," "transformational leadership," "driving school," and "implementation of the independent curriculum." With the theoretical perspective of Bernard Bass, the author analyzes the transformational leadership of madrasa heads in implementing the independent curriculum. This article aims to describe transformational leadership through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This leadership style is suitable for overcoming the challenges of changing curriculum policies because it has a positive and dynamic impact on the work environment.